The Impact of Information Technology Adoption and Strategic Partnerships Through Supply Chain Integration on Project Performance - Dimas Maulana; Ritman Miko Hartanto; Ibrahim Bahasoan; Rano Kartono Rahim (International Journal Labs, 2025)
This study addresses the persistent issue of construction project delays in Indonesia, proposing information technology (IT) adoption and strategic partnerships as key solutions to enhance project performance. Despite substantial infrastructure investment through the Proyek Strategis Nasional (PSN) program, construction delays remain a critical challenge, which cause cost overruns and suboptimal development outcomes. The research objective is to examine how IT adoption and strategic partnerships influence project performance, both directly and indirectly through supply chain integration, within state-owned construction enterprises (BUMN). The study employed a quantitative approach using questionnaires distributed through purposive sampling to 160 managers in five major construction BUMNs, followed by instrument testing using Smart PLS 4.1.1.4 software, including Outer Model Test, Inner Model Test, General Bias Test, and Hypothesis Test. The results demonstrate that: (a) Information Technology Adoption positively and significantly affects Supply Chain Integration ( -value = 4.592, -value = 0.000); (b) Strategic Partnership positively and significantly affects Supply Chain Integration ( -value = 6.501, -value = 0.000); (c) Information Technology Adoption positively and significantly affects Project Performance ( -value = 3.662, -value = 0.000); (d) Strategic Partnership has a negative and insignificant effect on Project Performance ( -value = 0.561, -value = 0.575); (e) Supply Chain Integration positively and significantly affects Project Performance ( -value = 5.379, -value = 0.000). The mediation analysis reveals that Supply Chain Integration serves as a critical mediating mechanism through which both IT adoption and strategic partnerships indirectly enhance project performance. These findings contribute to supply chain management theory by demonstrating that technological and relational capabilities must be integrated through supply chain processes to achieve optimal project outcomes.